USING HERRINGBONE AND SQ4R TECHNIQUES TO IMPROVE STUDENTS' ENGLISH READING COMPREHENSION THROUGH TEACHING AND LEARNING OF ENGLISH AT SMK NEGERI 1 MAKASAR - Lisna Wati; Kisman Salija; Munir Munir (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study's purpose was to find out how the Herringbone and SQ4R techniques could be used to help SMK students' reading comprehension. Quantitative experimental research methods and quasi-experimental research methods are used in this study. Students in class XI at SMK Negeri 1 Makassar during the odd semester of the academic year 2022/2023 made up the population in this study. For the purpose of evaluating how the Herringbone and SQ4R approaches affect students' English reading comprehension, the population was chosen at random. The pre-test, treatment, and post-test are the study's instruments. The Herringbone Technique was effective in enhancing the reading comprehension of students based on data analysis outcomes and computation. This is evident from the findings that the post-treatment average student scores fell into the "good" group whereas the pre-treatment average student scores fell into the "poor" category. This demonstrates that students' average post-test scores after treatment are greater than their average scores prior to treatment (pre-test). On the other hand, SQ4R was thought to be less successful in enhancing pupils' reading comprehension. One student's score declined from the post-test to the pre-test, and one student's score remained the same, as evidenced by the findings of the average scores of the students' pre-test and post-test were the same between pre-test and post-tests.Keywords— using Herringbone Technique, SQ4R, level of reading comprehension, and reading comprehension.